If a joint is hot it's not the time: health professionals' views on developing an intervention to promote physical activity in rheumatoid arthritis. Issue 11 (22nd May 2017) - Larkin, Louise; Gallagher, Stephen; Fraser, Alexander; Kennedy, Norelee
Abstract: Purpose: The study aimed to explore the views of health professionals on (i) physical activity in people who have rheumatoid arthritis (RA) and (ii) the design of an intervention to promote physical activity in this population. Method: We used a qualitative methodology and conducted 14 interviews (rheumatologists n  = 7, physiotherapist n  = 4, clinical nurse specialists n  = 3). Interviews were transcribed verbatim and analyzed using thematic analysis. Results: Three key themes were generated: " Personal opinions", "Supporting physical activity" and "An ideal world" . Although health professionals viewed physical activity as important, recommending it to people who have RA was largely based on persons' disease status rather than empirical evidence. Resources were highlight as a key challenge to interventions in clinical practice. Supporting physical activity through provision of information, goal setting and monitoring was also discussed. Conclusion: Health professionals believe physical activity is important for people who have RA, although there is uncertainty regarding physical activity recommendations for this population. Thus, there is scope to increase health professionals' knowledge of recent evidence. Views varied on how an intervention to promote physical activity should be delivered, but consideration of barriers to delivery in clinical practice is important. Implications for Rehabilitation: Physical activity is an important aspect of disease management for people who have rheumatoid arthritis. Health professionals need to acknowledge the "mixed messages" received by people who have RA about being physically active thus further education for health professionals is suggested to standardize physical activity advice in clinical practice. Health professionals may benefit from education about behavior change theory and techniques. When designing future physical activity interventions consideration of the practical challenges of implementing research in a clinical setting is necessary.